The Long-Term Outcomes after Radical Prostatectomy of Patients with Pathologic Gleason 8–10 Disease - Dan Lewinshtein; Brandon Teng; Ashley Valencia; Robert Gibbons; Christopher R. Porter (Advances in Urology)
Background. We explored the long-term clinical outcomes including metastases-free survival and prostate cancer-specific survival (PCSS) in patients with pathologic Gleason 8–10 disease after radical prostatectomy (RP). Methods. We report on 91 patients with PCSS data with a median followup of 8.2 years after RP performed between 1988 and 1997. Cox regression and Kaplan-Meier analysis were used to evaluate year of surgery, pathologic stage, and surgical margin status as predictors of PCSM. Results. Median age was 65 years (IQR: 61–9), and median PSA was 9.7 ng/ml (IQR: 6.1–13.4). Of all patients, 62 (68.9%) had stage T3 disease or higher, and 48 (52.7%) had a positive surgical margin. On multivariate analysis, none of the predictors were statistically significant. Of all patients, the predicted 10-year BCR-free survival, mets-free survival, and PCSS were 59% (CI: 53%–65%), 88% (CI: 84%–92%), and 94% (CI: 91%–97%), respectively. Conclusions. We have demonstrated that cancer control is durable even 10 years after RP in those with pathologic Gleason 8–10 disease. Although 40% will succumb to BCR, only 6% of patients died of their disease. These results support the use of RP for patients with high-risk localized prostate cancer.